Growth, Employment, and Income Distribution in Argentina, 1990-2010 - Santarcangelo, Juan Eduardo (2015)
In spite of the fact that Argentina has experienced a process of high sustained growth that created four million jobs, income distribution did not register substantial changes. The aim of this paper is to analyze the relationship between growth, employment, and income distribution; to clarify under what conditions a virtuous cycle of growth and employment may come to not have substantial impacts on income distribution; and to address the challenges that the working class will face in the future.